Implementasi Internalisasi Nilai Profil Pelajar Pancasila pada Siswa SD dalam Perspektif Islam - Ahmad Adib Murtadlo; Hamidaturrohmah; Syailin Nichla Choirin Attalina (EduInovasi: Journal of Basic Educational Studies, 2024)
Problems with students' attitudes and moral decadence are increasingly common, making it necessary to optimize character education from an early age. One way that can be done is to implement the Pancasila Student Profile values. This research analyzes the implementation of the internalization of Pancasila Student Profile values ​​among students at SD Al Islam Pengkol, Jepara, using a descriptive qualitative approach. The main objective is to describe various strategies for internalizing Pancasila values ​​in the context of Islamic education. Data obtained through interviews, observation, and documentation analysis, shows that the values ​​of Pancasila—including the dimensions of Faith, Global Diversity, Mutual Cooperation, Independence, Critical Reasoning, and Creativity—can be internalized well in the school. Although there are obstacles from student background and parental understanding, schools have taken innovative steps to overcome this problem, such as teacher training and strengthening communication with parents. These findings indicate that the integration of Pancasila values ​​with an Islamic perspective makes a significant contribution to the formation of student character, creating individuals who are moral, responsible and able to contribute positively to society. It is hoped that this research can become a reference for the practice of character education in elementary schools.